Online Meat Marketing: Technical, Socio-Economic, and Regulatory Challenges: 10.5958/2581-6616.2020.00003.1 - Muthukumar, M.; Nair, Rakesh G.; Naveena, B. M.; Devatkal, Suresh K.; Mandal, P. K. (Journal of Meat Science, 2021)
Today’s consumers especially young population, millennials are no longer satisfied with the traditional food products and the way they are marketed. Rather they seek more variety, safety and convenience while purchasing the products. They have developed more dynamic, complex and differentiated demands. These changes in consumer behaviour have ignited the livestock industry to seek various ways to market their products, which suits the expectations and convenience of the customers. The lack of hygienic and quality product choices in the traditional ‘seller-centric market’ coupled with the demand for fresh, safe and hygienic meat are gradually modifying the consumer behaviour, especially in the urban meat market principally drive the e-commerce meat marketing in urban India. The e-commerce meat marketing has a superior supply chain management and hi-tech interventions technology interface than the offline options. This article reviews about various practical challenges faced by the online meat market including consumer’s preference, meat safety and quality.